Scooping Review: The Influence of Socioeconomic Status on Adolescent Fatherhood in the Bajo Tribe and Child Health - Rismanudin Rismanudin; Nur Setiawati Dewi; Megah Andriany (Indonesian Journal of Global Health Research, 2024)
The Bajo Tribe, known for its unique cultural heritage and lifestyle, presents an interesting case for examining the interplay between socioeconomic status and parenting practices among adolescent fathers. This demographic is increasingly relevant as adolescent fatherhood has implications for both child health outcomes and family dynamics. This review aims to synthesise existing literature on how socioeconomic factors influence adolescent fathers' parenting styles within the Bajo Tribe and the subsequent health outcomes for their children. Method: A systematic search was conducted using the PRISMA-SCR guidelines. Databases such as PubMed, Scopus, and Google Scholar were queried for peer-reviewed articles published within the last ten years that focus on socioeconomic status, adolescent fatherhood, and child health, particularly in indigenous communities. Inclusion criteria focused on qualitative and quantitative studies highlighting the Bajo Tribe. Preliminary findings suggest a significant correlation between lower socioeconomic status and adverse parenting practices among adolescent fathers, which in turn negatively affects child health outcomes. Key themes identified include limited access to resources, education levels, and community support systems that directly impact parenting efficacy. The findings highlight the urgent need for targeted interventions that address socioeconomic disparities to improve parenting practices among adolescent fathers in the Bajo Tribe, ultimately enhancing child health outcomes.